Occupational Health Hazards and Treatment Seeking Behavior of Salt Pan Workers in Kutubdia and Maheshkhali Islands of Cox’s Bazar, Bangladesh - Md Humayun Kabir; Md Amzed Hossen; Muhammad Ferdaus (Journal of the Asiatic Society of Bangladesh, Science, 2025)
This study aimed to illuminate the prevailing occupational health issues faced by salt pan workers in Kutubdia and Maheshkhali Islands of Cox’s Bazar, Bangladesh. Utilizing qualitative methodologies, the research conducted individual interviews, focus group discussions, and key informant interviews with salt farmers, and community leaders, and experts. Data were analyzed using thematic analysis method to explore demographic attributes, health status, challenges, and concerns of the workers. Findings revealed that salt farmers frequently encounter heat stresses, dehydration, respiratory health problems, musculoskeletal issues, dermatological problems, and vision-related complications. The study also highlighted the lack of access to protective equipment, inadequate medical facilities, and substantial treatment expenses faced by the workers. The study emphasizes the urgent need for multifaceted interventions, emphasizing access to protective gear, community awareness enhancement, collaborative efforts, and sustainable practices. Addressing the occupational health challenges faced by salt pan workers in Kutubdia and Maheshkhali Islands requires concerted efforts from stakeholders, policymakers, and community leaders. J. Asiat. Soc. Bangladesh, Sci. 51(1): 87-102, June 2025